The Impact of YouTube and TikTok Influencers in the Customer Journey: An Empirical Comparative Study Among Generation Z Users - Silveira, Paulo Duarte (2022)
Trabalho apresentado em 2022 International Conference on Marketing and Technologies (ICMarkTech’22), 1-3 dezembro 2022, Santiago de Compostela, Espanha